Long Non-Coding RNA SNHG1 Regulates the Wnt/β-Catenin and PI3K/AKT/mTOR Signaling Pathways via EZH2 to Affect the Proliferation, Apoptosis, and Autophagy of Prostate Cancer Cell - Chen, Junyi; Wang, Fubo; Xu, Huan; Xu, Lingfan; Chen, Dong; Wang, Jialiang; Huang, Sihuai; Wen, Yiqun; Fang, Longmin (Frontiers in Oncology, 2020)
Background Prostate cancer (PCa) is the most common malignant cancer in western developed countries, which has seriously threatened the life style and life quality of men. Its pathogenesis and causes remain indistinct. Currently, it is found that lncRNA-SNHG1 (SNHG1) is highly expressed in multiple tumors with proto-oncogene effect, but its function and mechanism in PCa need to be further studied. Methods The expression of SNHG1 and EZH2 was detected by RT-qPCR in the 20 pairs of PCa tissue, adjacent tissue and PCa cell lines. They were transfected with siRNA NC, SNHG1 siRNA, EZH2 siRNA, SNHG1 siRNA+empty, and SNHG1 siRNA+EZH2 overexpression. Then, MTT and colony formation assay were used to detect the proliferation and cloning ability of PCa cells LNCaP and PC3. Transwell and flow cytometry were used to measure cell migration and invasion ability and apoptosis level respectively. Immunofluorescence was used to detect the LC3 spot formation. Western blot was used to detect the expression of the autophagy-related proteins, and PI3K/AKT/mTOR and Wnt/β-catenin signaling pathway related proteins. Finally, in vivo nude mice tumorigenesis experiment to explore the effect of SNHG1 expression on PCa. Results We found that SNHG1 and EZH2 were up-regulated in PCa tissue and cells. The expression of SNHG1 and EZH2 was positively correlated. RNA pull down and RNA IP assay further confirmed that SNHG1 bound to EZH2. The proliferation, colony formation, migration and invasion of LNCaP and PC3 cells were significantly reduced with the interference with SNHG1or EZH2 compared with the control group. The related proteins of Wnt/β-catenin and PI3K/AKT/mTOR signaling pathway were significantly reduced after the interference with SNHG1 or EZH2; after simultaneous interference with SNHG1 and overexpression of EZH2, the functional effects on LNCaP and PC3 cells interfered with SNHG1 were reversed. These results were also confirmed in vivo nude mice tumor formation experiments. Conclusions This study reveals that lncRNA-SNHG1 regulates Wnt/β-catenin and PI3K/AKT/mTOR signaling pathways via EZH2 gene to affect proliferation, apoptosis and autophagy of PCa cells. This experiment provides ideas and experimental basis for the improvement and treatment of PCa.